Non-alcoholic fatty liver disease in women – Current knowledge and emerging conceptsKey points - Pei Chia Eng; Roberta Forlano; Tricia Tan; Pinelopi Manousou; Waljit S. Dhillo; Chioma Izzi-Engbeaya (JHEP Reports, 2023)
Summary: Non-alcoholic fatty liver disease (NAFLD) is a major cause of liver disease worldwide, affecting up to 30% of adults. Progression to non-alcoholic steatohepatitis (NASH) is a key risk factor for cirrhosis, hepatocellular carcinoma and cardiovascular events. Alterations in reproductive hormones are linked to the development and/or progression of NAFLD/NASH in women. Women with polycystic ovary syndrome and those with oestrogen deficiency are at increased risk of NAFLD/NASH, with higher mortality rates in older women compared to men of similar ages. NAFLD/NASH is currently the leading indication for liver transplantation in women without hepatocellular carcinoma. Therefore, a better understanding of NAFLD in women is needed to improve outcomes. In this review, we discuss the hormonal and non-hormonal factors that contribute to NAFLD development and progression in women. Furthermore, we highlight areas of focus for clinical practice and for future research.